Re-irradiation to the prostate using stereotactic body radiotherapy (SBRT) after initial definitive radiotherapy – A systematic review and meta-analysis of recent trials - Christina Schröder; Hongjian Tang; Bianca Lenffer; André Buchali; Daniel Rudolf Zwahlen; Robert Förster; Paul Windisch (Clinical and Translational Radiation Oncology, 2024)
Background: There is increasing data on re-irradiation to the prostate using stereotactic body radiotherapy (SBRT) after definitive radiotherapy for prostate cancer, with increasing evidence on prostate re-irradiation using a C-arm LINAC or an MR LINAC in recent years. We therefore conducted this systematic review and meta-analysis on prostate re-irradiation including studies published from 2020 to 2023, to serve as an update on existing meta-analysis. Methods: We searched the PubMed and Embase databases in October 2023 with queries including combinations of “repeat”, “radiotherapy”, “prostate”, “re-irradiation”, “reirradiation”, “re treatment”, “SBRT”, “retreatment”. Publication date was set to be from 2020 to 2023. There was no limitation regarding language. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. After data extraction, heterogeneity testing was done by calculating the I2. A random effects model with a restricted maximum likelihood estimator was used to estimate the combined effect. Funnel plot asymmetry was assessed visually and using Egger’s test to estimate the presence of publication and/or small study bias. Results: 14 publications were included in the systematic review. The rates of acute ≥ grade 2 (G2) genitourinary (GU) and gastrointestinal (GI) toxicities reported in the included studies ranged from 0.0-30.0 % and 0.0–25.0 % respectively. For late ≥ G2 GU and GI toxicity, the ranges are 4.0–51.8 % and 0.0–25.0 %. The pooled rate of acute GU and GI toxicity ≥ G2 were 13 % (95 % CI: 7–18 %) and 2 % (95 % CI: 0–4 %). For late GU and GI toxicity ≥ G2 the pooled rates were 25 % (95 % CI: 14–35 %) and 5 % (95 % CI: 1–9 %). The pooled 2-year biochemical recurrence-free survival was 72 % (95 % CI: 64–92 %). Conclusions: SBRT in the re-irradiation of radiorecurrent prostate cancer is safe and effective. Further prospective data are warranted.